Phytochemical Screening of Ethanol Extract on Stems, Leaves and Roots of Citronella Grass (Cymbopogon nardus L) - Rofiatun Solekha; Putri Ayu ika Setiyowati; Sri bintang Sahara Mahaputra Kusumanegara; Chandra Tri uliana Sari (BEST Journal (Biology Education, Sains and Technology), 2022)
Citronella grass is a plant that belongs to the rhizome group. In its application, lemongrass is widely used for both food, medicine and aromatherapy needs. The various benefits of lemongrass are interesting to research about the content of compounds in lemongrass. The purpose of this study is to provide information about screening for chemical compounds in the ethanol extract of citronella (Cimbopogon nardus L). This research method is by way of Phytochemical Screening test, namely Alkaloids with Mayer, Dragendorff, and Bouchardat reagents. Flavonoid test with Shinoda test, tannin test with gelatin test, saponin test with foam test, terpenoid/steroid test with Liebermann-Burchard reagent. The results showed that phytochemical screening showed the presence of several compounds in the serum, namely alkaloids, tannins, saponins, triterpenoids and flavonoids in every member of the plant body, namely stems, roots and leaves, but did not contain steroids in the roots, stems and leaves.